2020
DOI: 10.3390/rs12081248
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Plant Functional Diversity Using the Reflectance and Echo from Space

Abstract: Plant functional diversity (FD) is an important component of biodiversity. Evidence shows that FD strongly determines ecosystem functioning and stability and also regulates various ecosystem services that underpin human well-being. Given the importance of FD, it is critical to monitor its variations in an explicit manner across space and time, a highly demanding task that cannot be resolved solely by field data. Today, high hopes are placed on satellite-based observations to complement field plot data. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 65 publications
(78 reference statements)
1
17
0
Order By: Relevance
“…Active remote sensing technologies such as Sentinel‐2 satellites, synthetic active radar (SAR) and light detection and ranging (LiDAR) instruments help to monitor plant traits at very high resolutions (e.g. 10 m) and spatial extents (Durán et al 2019, Ma et al 2020). For example, Durán et al (2019) used both imaging spectroscopy and foliar traits to estimate functional diversity in tropical forests across a large elevation gradient (215–3537 m) in South America.…”
Section: Towards An Understanding Of Functional Diversity and Species...mentioning
confidence: 99%
“…Active remote sensing technologies such as Sentinel‐2 satellites, synthetic active radar (SAR) and light detection and ranging (LiDAR) instruments help to monitor plant traits at very high resolutions (e.g. 10 m) and spatial extents (Durán et al 2019, Ma et al 2020). For example, Durán et al (2019) used both imaging spectroscopy and foliar traits to estimate functional diversity in tropical forests across a large elevation gradient (215–3537 m) in South America.…”
Section: Towards An Understanding Of Functional Diversity and Species...mentioning
confidence: 99%
“…Shifts in the content of photosynthetic pigments are related to the long-term variability of plants. It is known that the composition of photosynthetic pigments is very variable for different species [150,161]; this composition changes regarding the individual development of the plant [162][163][164], and it can be strongly dependent on local environmental conditions [161]. Particularly, the mineral nutrition is an important factor influencing concentrations of pigments in plants; e.g., changes in the nitrogen nutrition can influence concentrations of photosynthetic pigments and the content of RUBISCO, which is the key photosynthetic enzyme [7,[165][166][167][168].…”
Section: Variability Of Plantsmentioning
confidence: 99%
“…However, forest sites where crown shapes, in particular, (and the amount of leaf area per crown volume) differ more between tree species will be more difficult to analyze and will require a closer look. In this case, our method could be extended toward a linear combination of multiple leaf-tree matrices (one for each dominant tree species) if information on the species composition is available (e.g., by optical sensors) [55,56]. A recent study [31] demonstrated how stem diameter distributions of different plant functional types can be derived based on site-specific calibration.…”
Section: Strengths and Limitations Of The Presented Approachmentioning
confidence: 99%